Hui Medicine Moxibustion Promotes the Absorption of Lumbar Disc Herniation and the Recovery of Motor Function in Rats through Fas/FasL Signaling Pathway. (23rd July 2022) - Xu, Jianfeng; Luo, Qiang; Song, Junyao; Zhang, Yanming; Wang, Yingxu; Yang, Lei; Sha, Yinyin; Sun, Bowen; You, Na; Tian, Xinbao; Lin, Ruizhu; Wu, Yongli
Abstract : Objectives . To study the resorption of the herniated lumbar disc (RHLD) and its mechanism in the SD rats of lumbar intervertebral disc herniation treated with Hui medicine moxibustion (HMM). Methods . Forty SD rats were randomly divided into four groups, normal group, lumbar disc herniation (LDH) group, HMM group, and antagonist (HMM+Met12) group, with 10 rats in each group. The rat model of LDH was prepared with the method of lumbar epidural emplacement of the caudal intervertebral disc. In the HMM group and HMM+Met12 groups, 4 weeks after modeling, HMM therapy was performed in the lumbar spine for 3 months with 1 time per day and 20 min each time, the samples were collected 8 weeks after the treatment. The histological degeneration was observed through HE staining, and the neovascularization of intervertebral disc tissues was detected by the expression of CD34 and vascular endothelial growth factor (VEGF). The apoptosis of nucleus pulpous cells was detected by TUNEL assay, and the activity of caspase-3, -8, and -9 and extracellular matrix enzymes was detected by western blotting. Results . HMM treatment significantly improved the behavioral ability of rats with LDH surgery. The morphological structure was obviously destroyed in the LDH group, but disc structure was significantly repaired in the HMM group, and mild structure alterations were observed in the HMM+Met12 group. Higher levels of CD34 and VEGF were detected in the HMM group indicating that neovascularization is formed. The expression level of FasL was significantly increased in the HMM group. The protein expression levels of cleaved-caspase-3, cleaved-caspase-8, and cleaved-caspase-9 in nucleus pulposus (NP) tissues were also elevated when treated with HMM, and the TUNEL staining showed the same results. The protein expression levels of matrix metalloproteinases- (MMP-) 1, MMP-2, MMP-3, MMP-13, and ADAMTS-4 were markedly promoted in the HMM group. Met12, a small peptide antagonist of FasL, significantly reduced the effects of HMM. Conclusion . HMM can promote the formation of neovascularization of lumbar intervertebral disc, support the apoptosis of NP cells through Fas/FasL signaling, and regulate the degradation of extracellular matrix enzyme, which then accelerates the absorption of lumbar intervertebral disc herniation and the recovery of motor function in rats.